CONSUMPTION OF ANTIBIOTICS AS SELF-MEDICATION FROM OVER-THE-COUNTER PURCHASE: AN EMPIRICAL STUDY ARUNKUMAR - S, Arunkumar; S, Kumar Chandar; Nr, Vembu; G, Abirami (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The primary objective of this study is to find the reasons behind the practice of self-medication (SM) by the people with over-the-counter (OTC) drugs which are usually available in all medical stores. Methods: This article presents an empirical view of SM practice with OTC drugs. The research design of the study is descriptive, and the population of the study is customers who buy OTC drugs. The target population of this research is the common public who are all having the possibility to consume OTC drugs ever. The sampling technique used for this study is a systematic random sampling, and the sample size is 144. An instrument used for collecting data is a self-administered questionnaire and personal interview with the pharmacists. The data were analyzed using descriptive statistics. Results: The study results that most of the OTC customers consider SM is not a good practice, even though they practice SM of antibiotics in certain circumstances, due to reasons such as time-saving, convenience, cost saving, avoid waiting time to consult a doctor, easy and quick availability of antibiotics in neighbourhood drug stores, etc. Conclusion: The study concludes the reasons behind the SM practice and some remedies to overcome OTC drug-related problems from SM.Â 